Water-Borne Diseases, Cost of Illness and Willingness to Pay for Diseases Interventions in Rural Communities of Developing Countries - A Malik; A Yasar; AB Tabinda; M Abubakar (Tehran University of Medical Sciences, 2012)
Background: Almost one third of the global population is living in developing South Asia where disease occurrence is high especially in rural areas and people are unaware of water-borne diseases and cost of illness. Methods: The quantitative approach involved questionnaire based study (n=50 households). The community awareness, the occurrence of water-borne diseases with related cost of illness and community participation for the introduction of health interventions for water-borne diseases were evaluated through cross-tabulations, correlations, and ANOVA. Results: Majority (40%) of the community had no knowledge of water-borne diseases except some had little knowledge of diarrhea and typhoid.  Diarrhea followed by stomach diseases was widespread in the community. Population below poverty level was bearing the cost of illness around US$ 0.6-1.2 (Rs 50-100) per day followed by low and average income level with direct cost of US$ 2.3 (Rs 200) per day. The indirect cost of illness had showed increasing trend between US$ 2.3-4.7 (Rs 200-400) per day with increase in income levels. Maximum willingness to pay (WTP) for water supply and sewerage system was US$ 3.6 (Rs 300) and US$ 1.2 (Rs 100) per month respectively. Income and water supply demand was strongly correlated with acceptability to pay for the facilities (r = 0.319, 0.307; P< 0.05). Income had a strong influence on WTP for water and sewerage system (r = 0.805, 0.797; P< 0.05). Conclusion: To maintain rural health, water-borne diseases can be reduced by introducing health interventions like proper water and sanitation facilities.